Growth Performance of Smooth Marron (Cherax cainii) Fed Different Dietary Protein Sources - Ishaaq Saputra; Ravi Fotedar (Journal of Aquaculture and Fish Health, 2021)
Fish farming including freshwater crayfish still has a dependency on the availability of fish meal as the main source of protein in feed. The purpose of this study was to evaluate alternative protein sources including poultry by-products, feather meal, lupine flour, soybean meal and meat, and bone meal for smooth marron (Cherax cainii) freshwater crayfish feed. A total of 150 juvenile marrons (9.09 ± 0.21 g) were kept for 90 days and distributed into 15 rearing tanks consisting of five treatments with three replications. The results indicated that there was no significant difference in the increase in biomass, survival rate, moulting rate (weight), feed efficiency ratio, and feed digestibility (P> 0.05). However, marron juvenile fed with a protein source of poultry by-products meal had the highest specific growth rate (0.31 ± 0.05 g / day). In addition, marron fed with fish meal protein resulted a significant increase in carapace length (P <0.05). Based on the digestibility test, it was found that the digestibility level of the feed ranged from 76.39 ± 0.01 - 79.11 ± 0.01% and replacement of fish meal had no significant effect on dry matter digestibility (P> 0.05). Overall, the results of this study indicate that the general growth performance of marron is not affected by the replacement of fish meal in the feed. Alternative protein materials can be used as a protein source to replace fish meal in marron feed so that the use of fish meal can be reduced.